One summer: America 1927 - Bryson, Bill (London : Transworld, 2014)
n summer 1927, America had a booming stock market, a president who worked just four hours a day (and slept much of the rest), a devastating flood of the Mississippi, a sensational murder trial, and an unknown aviator named Charles Lindbergh who became the most famous man on earth.
Keywords: Social conditions; Manners and customs; United States